Association of serum Interleukin-8 level with lymph node metastasis and tumor recurrence in gastric cancer - Li, Xiang; Xie, Guiping; Zhai, Jing; He, Yani; Wang, Tongya; Wang, Yaohui; Shen, Lizong (Frontiers in Oncology, 2022)
The level of pretherapeutic serum interleukin-8 (sIL-8) has been demonstrated to correlate with chemoresistance in gastric cancer. However, its clinicopathological significance of sIL-8 in gastric cancer remains unknown. Herein, a total of 335 patients diagnosed with gastric adenocarcinoma were enrolled. The clinicopathological features were collected, and the sIL-8 levels were measured using enzyme-linked immunosorbent assay. The sIL-8 levels ranged from 1.48 pg/ml to 1025.22 pg/ml with > 15.41 pg/ml defined as high according to the receiver operating characteristic analysis. sIL-8 levels were strongly associated with Lauren classification and tumor recurrence. High sIL-8 correlated with lymph node metastasis (LNM) in the intestinal- and diffuse-type tumors and acted as an independent risk factor for LNM in both types. Patients with high sIL-8 levels had worse relapse-free survival than those with low sIL-8 levels. High sIL-8 level was associated with tumor relapse in the intestinal- and diffuse-type tumors, and was also an independent risk factor in the intestinal- and mixed-type tumors. Further analysis revealed that sIL-8 levels were positively associated with LNM and tumor relapse in patients with negative carcinoembryonic antigen (CEA), but not in those with elevated serum CEA levels. In conclusion, this retrospective study demonstrated that the pretherapeutic sIL-8 level has predictive value for LNM and tumor recurrence, and may serve as a potential tumor marker in gastric cancer.